El juego colaborativo para la construcción de habilidades blandas en los niños de educación inicial subnivel 2 de la Unidad Educativa Martiniano Guerrero Freire, ciudad de Riobamba - Changoluisa Nuñez, Adriana Lizbeth (2025)
This research project, entitled “El juego colaborativo para la construcción de habilidades blandas en los niños de educación inicial 2 de la Unidad Educativa Martiniano Guerrero Freire perteneciente a la ciudad de Riobamba,” has the main objective of determining the importance of collaborative play in the development of soft skills in children in early childhood education 2. is based on bibliographic references selected from reliable sources such as these, journal articles, university repositories, books, and websites. It has a qualitative approach with a descriptive level of research, for which the data collected was analyzed. The technique used was observation, and the instrument was an observation sheet consisting of 10 indicators and 3 assessment scales: initiated, in process, and acquired. Thirty students were involved, including 13 girls and 17 boys. The results obtained show that collaborative play does influence the development of soft skills at the initial level and that some students have difficulty relating to their peers, while others do not follow the rules during activities. Given these results, it is concluded that collaborative games are essential for the development of soft skills and that, in order to reinforce them, cooperative games should be used on a daily basis so that children can adapt without any difficulty and have good socio-emotional development throughout their lives.